Antioxidant, Antiproliferative, Antibacterial, and Antimalarial Effects of Phenolic-Rich Green Tea Kombucha - Udielle Vermelho Lacerda; Carolina Vargas Pereira da Costa; Rodrigo Rezende Cardoso; Carolina Thomaz dos Santos D’Almeida; Mariana Araújo Vieira do Carmo; Amanda dos Santos Lima; Laura da Silva Cruz; Amanda Bubula de Souza; Philipe Oliveira Fernandes; Vinícius Gonçalves Maltarollo; Mariana Simões Larraz Ferreira; Luciana Azevedo; et al. (Beverages, 2024)
Green tea kombucha, produced using a green tea (Camellia sinensis) grown in Brazil, was characterized and its in vitro bioactive properties were evaluated. Overall, 92 phenolic compounds were identified (70.7% flavonoids, 25% phenolic acids, 2.2% lignans, and 1.1% other polyphenols), contributing to the observed high antioxidant capacity. The major phenolics identified were gallocatechin, catechin 5-O-gallate, and epicatechin. Green tea kombucha exhibited antibacterial activity against all tested bacteria, being more effective against Salmonella spp. In addition, green tea kombucha demonstrated antimalarial activity against both chloroquine-sensitive and chloroquine-resistant strains of Plasmodium falciparum, and antiproliferative activity against cancer cell lines A549, HCT8, HepG2, and HUVEC. Additionally, it presented antioxidant properties by effectively reducing the generation of reactive oxygen species (ROS) and provided protection to erythrocytes against AAPH-induced oxidative stress. Thus, green tea kombucha is abundant in antioxidants and possesses intriguing bioactive properties that can be investigated by both the food and pharmaceutical sectors.